What are we fighting for? : a radical collective manifesto - Campagna, Federico; Campiglio, Emanuelle (Pluto Press, 2012)
The age of austerity has brought a new generation of protesters on to the streets across the world. As the economic crisis meets the environmental crisis, millions fear what the future will bring but also dare to dream of a different society. What We Are Fighting For tries to answer the question that the mainstream media loves to ask the protesters. The first radical, collective manifesto of the new decade, it brings together some of the key theorists and activists from the new networked andcreative social movements. Contributors include Owen Jones, David Graeber, John Holloway, Nina Power, Mark Fisher, Franco Berardi Bifo and Marina Sitrin. Chapters outline the alternative vision that animates the new global movement from new economics and new governance to new public and new social imagination. The book concludes by exploring new tactics of struggle.